2012
DOI: 10.2478/v10316-012-0022-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Mission Statement and Company Performance

Abstract: Mission statement is a managerial tool which has the power of directing the behaviour in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 25 publications
0
31
0
1
Order By: Relevance
“…In other words, the existence of a mission and its transparency has become essential for the successful functioning of any organization as a whole. In their work, Smith et al (2003) highlight some studies reporting that after the creation and introduction of mission statement, company performance increases for about 50% (Dermol, 2012). Bart et al (2001) found that mission statements could positively affect employee behavior which had a direct effect on firm financial performance (Kofi Darbi, 2012).…”
Section: The Effect Of Organizational Culture On Performancementioning
confidence: 99%
“…In other words, the existence of a mission and its transparency has become essential for the successful functioning of any organization as a whole. In their work, Smith et al (2003) highlight some studies reporting that after the creation and introduction of mission statement, company performance increases for about 50% (Dermol, 2012). Bart et al (2001) found that mission statements could positively affect employee behavior which had a direct effect on firm financial performance (Kofi Darbi, 2012).…”
Section: The Effect Of Organizational Culture On Performancementioning
confidence: 99%
“…Content analysis is therefore largely applied in the study of mission statements [15,30,31,34,38]. The analysis was performed using QDA-Miner (WordStat 6 QDA Miner 3 Simstat, Provalis Research, 1255 Robert Bourassa St, Suite #1604, Montreal, QC.…”
Section: Methodsmentioning
confidence: 99%
“…Following this idea, other contributions have sought to rename, enlarge, narrow, or redefine these components without changing the main meaning [32,33]. Typical words or expressions are mentioned in the mission statements; Dermol [34], for example, identified the most common words.…”
Section: Introductionmentioning
confidence: 99%
“…This is because of the statement"s specific content, rather than the mere existence of such a document, that makes a difference in firm performance (Bart & Hupfer, 2004). Yet, some authors point out, further empirical evidence is needed to support the links between the content of mission statements and performance outcomes (Dermol, 2012). A Study by (Omran, Atrill, & Pointon, 2002) mission significance found that there is no significant difference in shareholder returns between stakeholder-oriented and shareholder-oriented companies.…”
Section: Literature Reviewmentioning
confidence: 99%